The impact of electronic communication technology on written language - Hamzah, Mohd Sahandri Gani; Ghorbani, Mohammad Reza; Abdullah, Saifuddin Kumar (David Publishing Company, 2009)
Communication technology is changing things. Language is no exception. Some language researchers argue that language is deteriorating due to increased use in electronic communication. The present paper investigated 100 randomly selected electronic mails (e-mails) and 50 short messaging system (SMS) messages of a representative sample of international students in University Putra Malaysia (UPM) to find out the impact of these two specific modes of electronic communication on written language use. The e-mails from UPM International Students Association (UPM-ISA) yahoo group were content analyzed. A non-probability convenience sampling was used to select the 50 short message services sent to the researcher about different subject matters by Malaysian and international students at UPM. Then, they were also content analyzed. The results indicated that the language used in students’ e-mails and SMS messaging was full of spoken-like spelling, unconventional use of punctuation and abbreviations, and ungrammatical sentences. However, the more in-depth content analysis of the data revealed that the written language is being creatively adapted, developed, and enhanced to suit the conditions of the electronic communication age. Syntactical and lexical reductions are just strategies used to reduce effort, time and space.